45.0k views
4 votes
What is the steps for this equation.

What is the steps for this equation.-example-1
User Majella
by
4.3k points

1 Answer

2 votes

Answer:

see explanation

Explanation:

The steps required in the solution are

Add 1 to both sides

Take the square root of both sides

Subtract 3 from both sides

-----------------------------------------

Given

(x + 3)² - 1 = 35 ( add 1 to both sides )

(x + 3)² = 36 ( take the square root of both sides )

x + 3 = ±
√(36) = ± 6 ( subtract 3 from both sides )

x = - 3 ± 6, thus

x = - 3 - 6 = - 9 or x = - 3 + 6 = 3

User Milan Pithadia
by
4.7k points